2020
DOI: 10.3390/diagnostics10050278
|View full text |Cite
|
Sign up to set email alerts
|

Vitamin D-Binding Protein (Gc-Globulin) in Acute Liver Failure in Children

Abstract: This study aimed to analyse vitamin D-binding protein (Gc-globulin) serum levels in acute liver failure (ALF) in children in relation to disease outcomes and correlations with other known markers used to evaluate the severity of ALF. Our study included 34 children (mean age 4.87 ± 5.30 years) with ALF of different causes (metabolic, 26.47%; autoimmune, 23.53%; toxic, 20.59%; infection, 17.65%; unknown, 11.76%) and 30 children without any liver injury (mean age 6.11 ± 4.26 years). The outcome was poor in 14 pat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 36 publications
(71 reference statements)
0
12
0
Order By: Relevance
“…Beyond its classical role in calcium homeostasis, evidence arose from studies demonstrating antioxidant [ 82 , 83 , 84 ] and anti-fibrotic [ 85 , 86 , 87 ] functions, preventing inflammatory response [ 88 ] and intervening in immune-mediated injuries [ 3 , 8 , 89 , 90 , 91 , 92 , 93 , 94 ]. Treatment opportunities influence the prognosis and quality of life in patients with autoimmune diseases, and the immunomodulatory effects of vitamin D represent a potential supplementation therapy as vitamin D is deficient in patients suffering from autoimmune diseases [ 29 ].…”
Section: Introductionmentioning
confidence: 99%
“…Beyond its classical role in calcium homeostasis, evidence arose from studies demonstrating antioxidant [ 82 , 83 , 84 ] and anti-fibrotic [ 85 , 86 , 87 ] functions, preventing inflammatory response [ 88 ] and intervening in immune-mediated injuries [ 3 , 8 , 89 , 90 , 91 , 92 , 93 , 94 ]. Treatment opportunities influence the prognosis and quality of life in patients with autoimmune diseases, and the immunomodulatory effects of vitamin D represent a potential supplementation therapy as vitamin D is deficient in patients suffering from autoimmune diseases [ 29 ].…”
Section: Introductionmentioning
confidence: 99%
“…Studies on different clinical and laboratory parameters in ALF in children found that high TB level [3,44,57], increased INR [1,3,44,57], lower transaminases [58], young age [12,57,59], and encephalopathy [3,44,57] are prognostic factors for those who will need LT. Our team recently published a study on the role of Gc-globulin as a prognostic marker in children with ALF [25].…”
Section: Discussionmentioning
confidence: 99%
“…Until now, many factors proved to be possible prognostic markers for an unfavorable outcome in pediatric ALF: age under ten years, etiology (viral infections, Wilson's disease-WD), the presence of grade III/IV HE, a quick decrease in the liver volume or serum level of aminotransferases, increased level of bilirubin, severe coagulopathy (high International Normalized Ratio, INR, and decreased level of coagulation factors V and VII). Moreover, alpha-fetoprotein (AFP), serum phosphate, serum lactate, ammonia, vitamin D-binding protein were identified as possible prognostic factors in ALF [3,15,[22][23][24][25][26][27].…”
Section: Introductionmentioning
confidence: 99%
“…As mentioned, open‐heart surgery induces acute stress (Hoda et al, 2006) and a systemic inflammatory response (Borgermann et al, 2012; Canbaz et al, 2008; Czerny et al, 2000; Holmes et al, 2002), and systemic inflammation associates with a decrease in circulating 25(OH)D (Alemzadeh et al, 2012; Bang et al, 2011; Barker et al, 2012; Binkley et al, 2017; Dahl et al, 1998; De et al, 2014; Duncan et al, 2012; Ghashut et al, 2014; Grama et al, 2020 ; Henriksen et al, 2014; Krishnan et al, 2010; Louw et al, 1992; Reid et al, 2011; Vayrynen et al, 2016; Waldron et al, 2013). Although the mechanism regulating the decrease and confounding the interpretation of endogenous vitamin D levels during inflammation is obscure, various cytokines have been found to control the enzymatic machinery that accelerates the metabolism of 25(OH)D in vitro (Edfeldt et al, 2010; Hummel et al, 2013; Koeffler et al, 1985; Pryke et al, 1990; Reichel et al, 1987; Stoffels et al, 2006, 2007) and, therefore, could account for the decrease in circulating 25(OH)D concentrations when systemic levels are elevated.…”
Section: Discussionmentioning
confidence: 99%